2013
DOI: 10.1186/1756-3305-6-304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of cryptic and sympatric lymnaeid species from the Galba/Fossaria group in Mendoza Province, Northern Patagonia, Argentina

Abstract: BackgroundFreshwater lymnaeid snails can act as the intermediate hosts for trematode parasites such as the liver fluke Fasciola hepatica, that cause significant economic and biomedical burden worldwide, particularly through bovine fascioliasis. Transmission potential is tightly coupled to local compatibility with snail hosts, so accurate identification of lymnaeid species is crucial for understanding disease risk, especially when invasive species are encountered. Mendoza Province, in Argentina, is a center of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
3
18
0
1
Order By: Relevance
“…Our trees confirm the results of correa et al (2010,2011) and Standley et al (2013), in which G. cubensis together with G. neotropica form a sister group to G. viator, and the topology of the monophyletic Galba clade in our ITS-2 tree is basically the same as in the combined 18S/ITS-1/ITS-2 tree in barGueS et al (2011). On the other hand, the sequences of all three species in our trees are mixed within a single cluster which can be interpreted as a species cluster.…”
Section: Molecular Geneticssupporting
confidence: 81%
See 1 more Smart Citation
“…Our trees confirm the results of correa et al (2010,2011) and Standley et al (2013), in which G. cubensis together with G. neotropica form a sister group to G. viator, and the topology of the monophyletic Galba clade in our ITS-2 tree is basically the same as in the combined 18S/ITS-1/ITS-2 tree in barGueS et al (2011). On the other hand, the sequences of all three species in our trees are mixed within a single cluster which can be interpreted as a species cluster.…”
Section: Molecular Geneticssupporting
confidence: 81%
“…G. viator (d'Orbigny, 1835) is one of the fascioliasis vectors in Argentina (Standley at al. 2013) and Brazil (MedeiroS et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1). In Peru it was found in Lima (type locality) and Cajamarca (Bargues et al 2007(Bargues et al , 2012; in Venezuela it was found in Carabobo and Falcón (Bargues et al 2011) and in Argentina it was found in Mendoza, northern Patagonia (Mera y Sierra et al 2009;Standley et al 2013) and Buenos Aires, Central region (Sanabria et al 2012). Identities of all these records were achieved by molecular markers.…”
Section: Introductionmentioning
confidence: 93%
“…Email: jpujadas@ege.fcen.uba.ar Until recently, the specific identification of lymnaeid snails has been based exclusively on morphological characteristics of the shell, radula, and renal and reproductive organs (Hubendick 1951;Paraense 1976;Pointier et al 2004). However, reliance on these features failed to distinguish species with similar morphology (cryptic species) or variants within a single species (Pointier et al 2006;Standley et al 2013).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation